2011
DOI: 10.1029/2011gl049162
|View full text |Cite
|
Sign up to set email alerts
|

Imaging thunder

Abstract: We use a network of broadband microphones, including a 4‐element array, to locate the sources of thunder occurring during an electrical storm in central New Mexico on July 24th, 2009. Combined slowness search and distance ranging are used to identify thunder regions in three dimensions (out to 12 km) and for two overlapping frequency bands (1–10 and 4–40 Hz). Distinct thunder pulses are locatable and used to predict time‐of‐arrival to neighboring stations and to identify correlated phases across the network. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 19 publications
3
35
0
4
Order By: Relevance
“…This is a method for determining plane wave propagation directions, when measurements are conducted with a field of spatially separated instruments (Johnson et al 2011). The method is based on shifting the signals measured at each point in the array to the reference point with various values of slowness, the inverse of velocity, and summing them together.…”
Section: Discussionmentioning
confidence: 99%
“…This is a method for determining plane wave propagation directions, when measurements are conducted with a field of spatially separated instruments (Johnson et al 2011). The method is based on shifting the signals measured at each point in the array to the reference point with various values of slowness, the inverse of velocity, and summing them together.…”
Section: Discussionmentioning
confidence: 99%
“…Different authors [ Arechiga et al , ; Johnson et al , ; Qiu et al , ; Bodhika et al , ] compared the results of acoustic reconstructions of lightning channels to electromagnetic ones. It is to be noted that all these papers focused on the comparison of reconstructions from acoustic records and VHF sources detected by a LMA.…”
Section: Introductionmentioning
confidence: 99%
“…Except in Johnson et al [], reconstruction technique was adapted from the one developed by MacGorman et al []. Note that Johnson et al [] described the positions of reconstructed thunder sources through continuous spatial distributions representing the coherency of the positions. These authors confirmed that the location of acoustic sources corresponded with the location of VHF sources.…”
Section: Introductionmentioning
confidence: 99%
“…Further work is needed on the characteristics of volcanic thunder and its relation to lightning properties, such as frequency content of thunder and the nature of the lightning (intercloud or cloud to ground) (Johnson, ). Although we have shown correlations between volcanic thunder and lightning, the possibility for these phenomena to not be correlated is also interesting given that infrasonic thunder can arise from processes other than heating of the lightning channel, such as electrostatic source charging (Johnson et al, ). These results provide ways of distinguishing volcanic thunder from eruption acoustic signals and motivate improved methods of measuring volcanic thunder at close range and during explosive activity.…”
Section: Discussionmentioning
confidence: 79%